Perancangan ID Fan dan Cerobong pada Unit Pembangkit Listrik Tenaga Sampah - Purwanta, Wahyu; Suryanto, Feddy (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2018)
ABSTRACTThe problem for big cities in implementing the MSW disposal method is the Ã‚Â land availability. Hierarchically, a suitable method for solving this condition is not to dispose the MSW into the landfill but to treat it in the thermal processing, such as incineration. The bonus of this incineration is the heat dissipation that can be utilized to generate electricity. Burning MSW through incinerator that converts into energy is often called a Waste to Energy (WtE) or PLTSa. Ã‚Â Beside the benefit of the high temperature flue gas that can produce electricity, PLTSa also emits major pollutants in the flue gas such as particulates, SO2, NOx, CO, HCl, dioxins and furans. In order to meet the emission standards, the PLTSa design has to be equipped with APCDÃ¢â‚¬â„¢s such as cyclone, semi-dry scrubber and bag filter. ID fan withdraws the flue gas into the chimney before discharging it into the ambient air through the top exit of chimney. The main parameters in the design of the ID fan and chimney are the quantity, quality and temperature of the flue gas as well as the environmental parameters, such as air temperature, atmospheric stability, wind speed and direction.Ã‚Â The design of the chimney was carried out with a technical calculation approach, simulation of Gaussian dispersion model and the compliance of related regulations from the MoEF. In the design of PLTSa with a waste capacity of 350 tons/day, specification of the stack is 2.02 m diameter and the 70 m height whereas ID fan is 70,000 cfm flue gas flowrate, 400 BHP power, 80% mechanical efficiency and Ã‚Â 25 inch H2O pressure pump.Keywords: Waste-to-energy, flue gas, ID fan, chimneyABSTRAKSalah satu masalah bagi kota-kota besar dalam menerapkan metode pengolahan sampah adalah ketersediaan lahan. Secara hierarkis metode yang mampu memenuhi kondisi ini adalah pengolahan dengan metode termal sekaligus memanfaatkan buangan panas yang ada untuk membangkitkan energi listrik. Pembakaran sampah dengan insinerator yang merubah sampah menjadi energi ini sering juga disebut Ã‚Â Ã‚Â Pembangkit Listrik Tenaga Sampah (PLTSa). Salah satu hasil samping PLTSa adalah flue gasÃ‚Â yang temperaturnya tinggi serta mengandung polutan utama seperti partikulat, SO2, NOxÃ‚Â dan CO. Ã‚Â Agar memenuhi baku mutu emisi, Ã‚Â rancangan PLTSa dalam studi ini dilengkapi dengan unit cyclone, semi dry scrubber, bag filterÃ‚Â dan ID fanÃ‚Â serta cerobong sebagai unit pembuangan akhir flue gas. Sebagai unit akhir pembuang flue gasÃ‚Â ke lingkungan, peran cerobong sangat penting sehingga perlu beberapa pendekatan dalam perancangan. Parameter desain utama dalam perancangan cerobong adalah kuantitas, kualitas dan suhu dari flue gas serta parameter meterologis lingkungan seperti suhu udara, stabilitas atmosfer, kecepatan dan arah angin. Dalam perancangan cerobong pada studi ini dilakukan dengan pendekatan perhtiungan teknis, simulasi model dispersi Gaussian serta peraturan terkait dari Kementerian Lingkungan Hidup dan Kehutanan. Dalam rancangan PLTSa Ã‚Â dengan kapasitas olah sampah 350 ton/hari ditetapkan diameter cerobong 2,05 m dengan tinggi 70 m, serta diperlukan ID fanÃ‚Â sebagai pendorong flue gasÃ‚Â dengan spesifikasi Q = 70.000 cfm, BHP = 400, mechanical efficiencyÃ‚Â 80% dan static pressureÃ‚Â pompa = 25 inch H2O.Kata kunci: Sampah menjadi energi, gas buang, ID fan, cerobong